Lectures 5-6

Topics: basic proof methods


Give formal proofs of the following two statements.

  1. 1. There exists an integer \(x\) such that, for every integer \(y\), \(x +y = y\).

    Proof:
        1. Let \(x=0\). Note that \(x \in \mathbb{Z}\).
            2. Let \(y\) be an arbitrary integer.
            3. Then \(x+y = 0+y = y\) (by axioms of arithmetic)
        4. (\(\forall y \in \mathbb{Z}. x+y=y\)) is true (by generalization 2,3)
    5. (\(\exists x \in \mathbb{Z}.\forall y \in \mathbb{Z}. x+y=y\)) is true (by construction 1,4)

  2. 2. For every integer \(y\), there exists an integer \(x\) such that \(x + y = 0\).

    Proof:
        1. Let \(y\) be an arbitrary integer.
            2. Let x = -y. Note that \(x \in \mathbb{Z}\) since \(y \in \mathbb{Z}\)
            3. x + y = (-y)+y = 0 (by axioms of arithmetic)
        4. \((\exists x \in \mathbb{Z}. x+y=0)\) is true (by construction 2,3)
    5. \((\forall y \in \mathbb{Z}.\exists x \in \mathbb{Z}. x+y=0)\) is true (by generalization 1,4)

From the two questions above, notice that the order of the quantifiers changes the nature of the proofs.
To prove a proposition of the form \(\forall y \in D. \exists x \in C. p(x,y)\) (as in question 2), we pick an arbitrary element \(y\) in the domain \(D\) and we can use \(y\) to construct an \(x\) in \(C\).
However, when proving a proposition of the form \(\exists x \in C. \forall y \in D.p(x,y)\) (as in question 1), we must define \(x\) before we pick \(y\), so we cannot use \(y\) to construct \(x\).




  1. 3. Suppose that we have a statement of the form \((\forall x \in D. F)\). Suppose that we replace each occurrence of the variable \(x\) in formula \(F\) with the variable \(y\) to get a formula \(F'\). Are \((\forall x \in D. F)\) and \((\forall y \in D. F')\) equivalent?

    It depends whether or not the variable \(y\) occurs in \(F\). If \(y\) does not occur in \(F\), then \((\forall x \in D. F)\) and \((\forall y \in D. F')\) are equivalent.
    However, consider the following example:
    Let \(F = (x \textrm{ AND } ( \textrm{NOT } y))\). Then, \(F' = (y \textrm{ AND } (\textrm{NOT } y))\). Therefore, \(F'\) always evaluates to false. So, under any interpretation that sets \((\forall x \in D. F)\) to true, the statements \((\forall x \in D. F)\) and \((\forall y \in D. F')\) are not equivalent.




  1. 4. It is known that every non-zero rational number x has a multiplicative inverse, i.e., a rational number y such that xy = yx = 1. Give an informal proof that this inverse is unique.

    Use a proof by contradiction. Start by assuming that there exist two distinct inverses for x.

    Let a and b be two such distinct inverses. Try to show that \(a=b\).

    To obtain a contradiction, assume that there exist two distinct inverses for \(x\), say \(a\) and \(b\). Then, by definition of inverse, we know that \(ax=1\). Multiply both sides by \(b\) to get \(axb = b\). Again, by the definition of inverse, \(xb=1\). Substituting this into \(axb=b\), it follows that \(a=b\), which contradicts the fact that \(a\) and \(b\) are distinct.

  2. 5. Consider the following formal proof of the statement "the inverse of any non-zero rational number \(x\) is unique". The proof is correct, but would not receive a good grade on an assignment because it is missing the required justification at the end of each line. Fill in what is missing in each empty set of brackets (and hover your mouse over the blank space to reveal the correct answer).

        1. Consider any \(x \in \mathbb{Q}\)
             2. Assume \(x \neq 0\)
                  3. Assume \(\exists a \in \mathbb{Q}. \exists b \in \mathbb{Q}. [(a \neq b) \textrm{ AND } (ax = 1) \textrm{ AND } (bx = 1)]\)
                  4. Choose \(a,b \in \mathbb{Q}\) such that \(a \neq b\) and \(ax = 1\) and \(bx = 1\) (instantiation 3)
                  5. \(ax = 1 \textrm{ IMPLIES } axb = b\) (axiom of algebra)
                  6. \(axb = b\) (modus ponens 4,5)
                  7. \(bx = 1 \textrm{ IMPLIES } xb = 1\) (axiom of algebra)
                  8. \(xb = 1\) (modus ponens 4,7)
                  9 \(axb = b \textrm{ AND } xb = 1\) (proof of conjunction 6,8)
                  10. \((axb = b \textrm{ AND } xb = 1) \textrm{ IMPLIES } a=b\) (tautology)
                  11. \(a=b\) (modus ponens 9,10)
             12. \( \textrm{NOT}(\exists a \in \mathbb{Q}. \exists b \in \mathbb{Q}. [(a \neq b) \textrm{ AND } (ax = 1) \textrm{ AND } (bx = 1)])\) (contradiction 3,4,11)
        13. \( x \neq 0 \textrm{ IMPLIES } \textrm{NOT}(\exists a \in \mathbb{Q}. \exists b \in \mathbb{Q}.[ (a \neq b) \textrm{ AND } (ax = 1) \textrm{ AND } (bx = 1)]) \) (direct proof 2,12)
    14. \( \forall x \in \mathbb{Q}.x \neq 0 \textrm{ IMPLIES } \textrm{NOT}(\exists a \in \mathbb{Q}. \exists b \in \mathbb{Q}. [(a \neq b) \textrm{ AND } (ax = 1) \textrm{ AND } (bx = 1)]) \) (generalization 1,13)

Found an error? Send us an email